Multigene phylogeny and taxonomic revision of yeasts and related fungi in the Ustilaginomycotina - Wang, Q.-M. (Stud Mycol, 2015)
The subphylum Ustilaginomycotina (Basidiomycota, Fungi) comprises mainly plant pathogenic fungi (smuts). Some of the lineages possess cultivable unicellular stages that are usually classified as yeast or yeast-like species in a largely artificial taxonomic system which is independent from and largely incompatible with that of the smut fungi. Here we performed phylogenetic analyses based on seven genes including three nuclear ribosomal RNA genes and four protein coding genes to address the molecular phylogeny of the ustilaginomycetous yeast species and their filamentous counterparts. Taxonomic revisions were proposed to reflect this phylogeny and to implement the ‘One Fungus = One Name’ principle. The results confirmed that the yeast-containing classes Malasseziomycetes, Moniliellomycetes and Ustilaginomycetes are monophyletic, whereas Exobasidiomycetes in the current sense remains paraphyletic. Four new genera, namely Dirkmeia gen. nov., Kalmanozyma gen. nov., Golubevia gen. nov. and Robbauera gen. nov. are proposed to accommodate Pseudozyma and Tilletiopsis species that are distinct from the other smut taxa and belong to clades that are separate from those containing type species of the hitherto described genera. Accordingly, new orders Golubeviales ord. nov. with Golubeviaceae fam. nov. and Robbauerales ord. nov. with Robbaueraceae fam. nov. are proposed to accommodate the sisterhood of Golubevia gen. nov. and Robbauera gen. nov. with other orders of Exobasidiomycetes. The majority of the remaining anamorphic yeast species are transferred to corresponding teleomorphic genera based on strongly supported phylogenetic affinities, resulting in the proposal of 28 new combinations. The taxonomic status of a few Pseudozyma species remains to be determined because of their uncertain phylogenetic positions. We propose to use the term pro tempore or pro tem. in abbreviation to indicate the single-species lineages that are temporarily maintained.